Splenic Lymphangioma Mimicking Lymphomatous Involvement: A Case Report with Review of the Literature - Neda Soleimani; Fatemeh Pouraminaee; Mohammad Hossein Anbardar; Ali Bahador; Benyamin Rahimi; Sahand Mohammadzadeh; Fatemeh Aghakhaninejad; Mohammad Farahmand; Mahsa Hasani (Case Reports in Medicine)
Lymphangioma is a benign malformation of lymphatic vessels usually found in the head and neck areas or axilla. They may involve visceral organs with a lower percentage. Splenic lymphangioma is a rare tumor. This disease is often seen in children but may be diagnosed incidentally in adults. Most patients are asymptomatic, but in large and multifocal lesions, the patient may have some nonspecific symptoms such as abdominal pain, abdominal distention, nausea, vomiting, and loss of appetite. Physical examination may show no specific findings or detect palpable masses. The preoperative diagnosis of splenic lymphangioma is challenging. Histopathological evaluation and sometimes immunohistochemistry tests can result in a definitive diagnosis. In this study, we present an 18-year-old man, with Burkitt’s lymphoma who underwent laparotomy and total splenectomy as a result of cystic lesions discovered accidentally during imaging with the final diagnosis of splenic lymphangioma after histopathological evaluation.